Research on fatigue characteristics of conductive rod of high pressure bushing under different factors - Xiu Zhou; Tian Tian; Longcheng Dai; Jin Bai; Weidong Yang; Yan Luo; Liangliang Pan; Jiaying Yu; Jibing Li; Xianghui Chang; Dezhi Chen (AIP Advances)
As the most important part of the UHV DC transmission project, the capacity and voltage level of the transformer are continuously improved, and the technical difficulty and failure rate of its operation and maintenance are also increasing. The high voltage bushing of the UHV main transformer is widely used in substations, and its operational reliability directly affects the operational safety of equipment and the power grid. The conducting rod is the key component of the high voltage bushing. The quality of its electrical strength, mechanical structure, and thermal stability is crucial to the high voltage bushing of the UHV main transformer. Based on this, this paper studies the stress and fatigue life of the 750 kV high voltage bushing conductive rod. In the process of realization, the influences of different temperatures, different operating conditions, different processing technologies, and different assembly factors are considered. First, the finite element models of two different structures of high voltage bushing conductive rods with integrated forming structures and connecting structures are established, and the fatigue theory is analyzed. Second, the simulation research on the stress and fatigue life of the 750 kV high voltage bushing conductor rod with two structures under different factors is carried out, and the simulation results of the fatigue life of the 750 kV high voltage bushing conductor rod with different factors are given. Finally, the material properties of the high voltage bushing conductive rod were tested, and the simulation results were compared with the experiments to verify the correctness of the proposed scheme.